A Plastic Surgeon's Guide to the Temporomandibular Joint: Part II, Pathophysiology and Diagnosis. Issue 2 (June 2023) - Ibelli, Taylor J.; Greer, Madison; Le, John M.; Platt, Samantha; Doo, Florence; Mantilla-Rivas, Esperanza; Rottgers, S. Alex; Buller, Mitchell; Crowder, Hannah; Nasser, Jacob S.; Rogers, Gary F.; Taub, Peter J.
The temporomandibular joint (TMJ) is a ginglymoarthrodial joint that allows translational or sliding movement in the superior compartment and rotational or hinging movements in the inferior compartment. The articulation of both mandibular condyles with the glenoid fossa of the temporal bone is separated by a cartilaginous articular disk that allows the joint to undergo the functional movements involved in speech and mastication. Any anatomic disequilibrium of the TMJ can produce mechanical dysfunction and orofacial pain. The complexity of the TMJ necessitates a thorough understanding of the anatomy and physiology to diagnose and treat its pathology properly. The authors present the second of a three-part educational series on the TMJ, focusing on the pathophysiology and assessment of joint disorders.